Seleção de genótipos de batata-doce com potencial de uso das folhas para alimentação humana - Gama, André Boscolo Nogueira da (2020)
Leaves of Ipomoea potatoes (L) Lam. have desirable characteristics for human consumption, as they are productive, rich in nutrients and have medicinal functions. However, they are not a form usually explored in culture, requiring related research. Thus, the aim of this study was to select sweet potato genotypes with the potential to use leaves for human consumption. The experiment was carried out at Fazenda Palmital, in the municipality of Ijaci, belonging to the Federal University of Lavras (UFLA). 26 genotypes belonging to the UFLA Germplasm Bank and 4 commercial cultivars (Beauregard, Brazlândia Roxa, Princesa and Uruguaiana) were evaluated. A randomized block design with three replications and 10 plants per plot was used. Leaf colorations, branch productivity, useful leaf productivity, use of useful leaves, dry weight of useful leaves, latex production, total chlorophyll, pH, titratable acidity, soluble solids, total phenolics and anthocyanins of potato leaves were evaluated -candy. The roots were also evaluated for their skin and pulp color and total productivity. The data obtained were submitted to ANOVA (p≤0.05) and compared by the Scott-Knott test at 5% significance. Phenotypic and genotypic correlations were also estimated, in addition to genetic divergence through canonical variables and dendogram by the UPGMA method. The leaves have the potential to be used for human consumption. The characters related to colors, useful leaf productivity and bioactive compounds showed high variability and are relevant to meet commercial demand. The variables showed significant differences between the genotypes, except for dry matter, pH, titratable acidity and soluble solids. The genotypes 2018-12-252, 2018-19-464, 2018-28-556, 2018-37-864, 2018-37-869, 2018-53-1032, 2018-55-1153, 2018-55-1154, 2018-72-1401 e 2018-74-1507 are the most recommended for the use of leaves in human food because they present the best agronomic and chemical characteristics. The most relevant positive phenotypic correlations occurred between colorimetric characteristics and the production of branches and leaves, while the most expressive negative correlation occurred between the total chlorophyll content and the colorimetric characteristics. As for genetic correlations, the most significant was negative between pH and total titratable acidity. Regarding genetic divergence, the genotypes 2018-19-387, 2018-19-389, 2018-28-543, 2018-31-666, 2018-38-926, 2018-53-1032, 2018-61-1163, 2018-67-1321, 2018-74-1479, UFVJM-58, UFVJM-61, Beauregard, Brazlândia Roxa, Princesa e Uruguaiana were the most divergent.